1976
DOI: 10.1093/oxfordjournals.jbchem.a131307
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Stimulation by Retinol of Porcine Pancreatic Esterase Activity toward Esters of Short-chain Fatty Acids

Abstract: 1. Retinol exerted a remarkable stimulating effect (approx. 260% increase), essentially similar to that (300%) of phytol, on the so-called esterase activity displayed by crude pancreatic lipase [EC 3.1.1.3] toward true solutions of esters, but none of the typical lipase activity toward emulsions of water-insoluble esters. 2. Comparison of the stimulatory effects of retinol derivatives on the esterase activity revealed that retinyl acetate was the most active, being sustantially similar in effect to retinol; re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1982
1982
1983
1983

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We have thus far studied the isolation and characterization of the activator, which stimulates markedly the hydrolysis of triacetin (TAesterase activity) by a porcine pancreatic lipase preparation, from the marine brown alga Hizikia fusiformis (hiziki).l -8) It has been found that phytol 6 ) isolated from hiziki is a typical activator of this kind, and recently that parathion 9 ) as well as retinol 10 ) exhibits a remarkable stimulating action, essentially similar to that observed with phytol, on the TAesterase activity.…”
mentioning
confidence: 99%
“…We have thus far studied the isolation and characterization of the activator, which stimulates markedly the hydrolysis of triacetin (TAesterase activity) by a porcine pancreatic lipase preparation, from the marine brown alga Hizikia fusiformis (hiziki).l -8) It has been found that phytol 6 ) isolated from hiziki is a typical activator of this kind, and recently that parathion 9 ) as well as retinol 10 ) exhibits a remarkable stimulating action, essentially similar to that observed with phytol, on the TAesterase activity.…”
mentioning
confidence: 99%